1996
DOI: 10.1046/j.1365-3083.1996.d01-333.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyreactive IgA and IgM Autoantibodies in Human Colostrum

Abstract: Secretory antibodies against bacteria and viruses in human colostrum and milk are known to be important protective factors for the breast-fed infant. The authors have shown by enzyme immunoassay that colostrum contains IgA and IgM antibodies to a number of autoantigens: native DNA, actin, myosin, myoglobin, laminin, transferrin and thyroglobulin. These antibodies were polyspecific-those with anti-DNA reactivity immunopurified on a DNA-cellulose affinity column bound to a panel of self- and environmental antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
1
32
1
Order By: Relevance
“…The functions of these and other autoantibodies to tumor-associated and other selfAgs in healthy mothers and newborns need to be studied. It would be important to know whether the T cell repertoire in healthy subjects-the T cell homunculus-likewise contains clones potentially reactive to these particular self-Ags (23). In any case, the prevalence of highly reactive autoantibodies to tumor-associated self-Ags supports the idea that the healthy immune system is outfitted, even from birth, to express some form of tumor-associated immune reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of these and other autoantibodies to tumor-associated and other selfAgs in healthy mothers and newborns need to be studied. It would be important to know whether the T cell repertoire in healthy subjects-the T cell homunculus-likewise contains clones potentially reactive to these particular self-Ags (23). In any case, the prevalence of highly reactive autoantibodies to tumor-associated self-Ags supports the idea that the healthy immune system is outfitted, even from birth, to express some form of tumor-associated immune reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible with maternal transfer, the only isotype of these Abs detected in cord sera was IgG-IgM and IgA Abs to these Ags were found only in maternal sera. Note that some of the viral and bacterial Ags highly reactive with serum Abs were less reactive with milk Abs; thus, systemic and secretory immunization appear to differ (19)(20)(21)(22)(23).…”
Section: Antiforeign Pathogen Reactivitiesmentioning
confidence: 99%
“…We purified the Abs to CCR5 from pooled breast milk of both HIV-seropositive and -seronegative women by means of affinity chromatography on a synthetic peptide corresponding to a 20-amino acid region (II.E/C-CCR5) derived from the second extracellular loop of CCR5. This loop together with the N-terminal sequence (aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the first extracellular loop (aa 89 -102) is involved in the binding of gp120 and of natural CCR5 ligands to the CCR5 molecule (6,(11)(12)(13). We focused on the second extracellular loop of CCR5 that was shown to be immunogenic and induce a B and T cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk contains high amounts of immunoglobulins, predominantly of the secretory IgA (sIgA) 4 and to a lesser degree of the IgG and sIgM isotypes that are produced in the absence of deliberate immunization and independently of exposure to Ags. Most natural Abs in the breast milk of healthy women are self-reactive Abs (9,10).…”
Section: Natural Antibodies To Ccr5 From Breast Milk Block Infection mentioning
confidence: 99%
“…A pathological role for NAbs has been suggested in autoimmunity, tumor cell recognition, and atherosclerosis (3,9,20). It has been shown that human colostrum and saliva contain large amounts of S-IgA polyreactive NAbs (44). The natural humoral immunity of the female genital tract, however, has not yet been studied.…”
mentioning
confidence: 99%